Between Two Worlds: Promoting Identity Development in Middle School - Reimer, Kenneth (International Journal for Talent Development and Creativity, 2023)
This paper highlights a (2022) study conducted in a Canadian school division with middle school teachers. The purpose of this study was to learn what middle school teachers did to positively connect with their students. Due to COVID-related concerns, four participants were interviewed individually via zoom and asked to share strategies that they incorporated in the classroom and school to make these connections. Middle school teachers shared strategies and practices that facilitated identity development in their students. Participants in this study appeared to encourage identity development by encouraging introspection and extrospection in their classrooms. They recognized the importance of establishing class routines promoting self-regulation and developing empathy for others. They also created opportunities for students to discuss and learn about local and global topics in class. Their responses are compared and contrasted with past scholarship highlighting the importance of identity development for young people.